UV-Spectrophotometric Determination of Famciclovir in Pharmaceutical Formulations - SRINU BABU, G.; SARAT BABU, I.; KIRAN KUMAR, N.; YUGANDHAR, N.M.; A.I. RAJU, CH. (Asian Journal of Chemistry, 2010)
A simple, sensitive, spectrophotometric method in UV region has been developed for the determination of famciclovir in bulk and tablet dosage forms. Famciclovir shows maximum absorbance at 304 nm with apparent molar absorptivity of 5.8892 × 103 Lmol-1cm-1. Beer’s law was obeyed in the concentration range of 10-50 μg/mL. Results of the analysis were validated statistically and by recovery studies.